2020
DOI: 10.1016/j.psj.2020.09.045
|View full text |Cite
|
Sign up to set email alerts
|

Possible role of available phosphorus in potentiating the use of low-protein diets for broiler chicken production

Abstract: A total of 945 male Ross 308 broiler chicks were used in a growth study to explore the interaction between dietary crude protein concentration and available phosphorus. Nine experimental treatments were constructed factorially by offering low, medium, or standard protein concentrations without or with low, standard, or high available phosphorus. Diets were based on corn, wheat, and soybean meal and all nutrients other than protein/amino acids and available phosphorus were maintained at or above breeder guideli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…In this study, we observed increased serum P level in 16.5% CP diet. This result was consistent with the observation in broilers by Cowieson et al (2020) , who reported that serum P was decreased by low-protein diet, which is speculated to be a result of reduced dietary P level in low-protein diet. In the present study, the experimental diets had the same amount of P, and hence, the effect of dietary protein level on P metabolism needs to be investigated further.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we observed increased serum P level in 16.5% CP diet. This result was consistent with the observation in broilers by Cowieson et al (2020) , who reported that serum P was decreased by low-protein diet, which is speculated to be a result of reduced dietary P level in low-protein diet. In the present study, the experimental diets had the same amount of P, and hence, the effect of dietary protein level on P metabolism needs to be investigated further.…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, lower serum K levels in birds fed the RP diet might be attributed to the lower inclusion of soybean meal in the RP compared to the SP diet, as soybean meal is a rich source of K. The analysed mineral levels in the mixed feed confirm a lower K level for RP diets compared to SP diets in the current study. Cowieson et al (2020) observed increased plasma Ca level as dietary CP level decreased (from 21.5% and 19.5% to 17.5% and 15.5% in grower and finisher phases, respectively). The present study results were in line with those previously documented in the literature.…”
Section: Discussionmentioning
confidence: 83%
“…However, there were not many reports investigating the effects of feeding reduced-protein diets on bone morphology, strength, and mineralisation in birds during heat stress. Available data have shown that reducing dietary protein levels could increase serum Ca, Na, and Zn levels but decrease tibia Mn and Cu levels in broilers raised under standard conditions (Cowieson et al, 2020). Bone quality is one of the most important indicators to evaluate the broiler's health and welfare (Brickett et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, further research is warranted into bird performance response to protease in diets with low, but comparatively less extreme, amino acid concentrations. Moreover, Cowieson et al (2020) stated that supplementation of synthetic amino acids or enzymes alone cannot counteract the multiple issues associated with feeding low-protein diets to broiler chickens. For example, they observed improved FCR in low-protein diets as a consequence of increasing dietary available phosphorus level.…”
Section: Discussionmentioning
confidence: 99%